2020
DOI: 10.7150/jca.42736
|View full text |Cite
|
Sign up to set email alerts
|

TOP2A Promotes Tumorigenesis of High-grade Serous Ovarian Cancer by Regulating the TGF-β/Smad Pathway

Abstract: Background: High-grade serous ovarian cancer (HGS) is the most aggressive form of ovarian cancer due to its rapid spread, insidious onset, and early dissemination throughout the abdominal cavity. However, the molecular pathogenesis of HGS remains unclear. This study aimed to identify key pathogenic genes and explore the underlying molecular mechanisms of HGS using bioinformatics analysis and biological experiments. Methods: Two datasets were downloaded from the Gene Expression Omnibus databases to find differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 19 publications
1
31
0
Order By: Relevance
“…A lot of studies also suggest that involvement of carcinogenesis in various cancers (lung, liver, and breast cancer) is due to highly expressed TOP2A thereby causing slow prognosis in patients [ 31 33 ]. TOP2A also promotes tumorigenesis in ovarian cancer which regulates the TGF- β /Smad pathway; the expression of TOP2A was also found to correlate with poor survival of ovarian cancer patients and platinum resistance [ 34 , 35 ]. Our results have shown that upregulation of TOP2A in tissues of ovarian cancer is linked with poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…A lot of studies also suggest that involvement of carcinogenesis in various cancers (lung, liver, and breast cancer) is due to highly expressed TOP2A thereby causing slow prognosis in patients [ 31 33 ]. TOP2A also promotes tumorigenesis in ovarian cancer which regulates the TGF- β /Smad pathway; the expression of TOP2A was also found to correlate with poor survival of ovarian cancer patients and platinum resistance [ 34 , 35 ]. Our results have shown that upregulation of TOP2A in tissues of ovarian cancer is linked with poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“… 49 In ovarian cancer, TOP2A promotes tumorigenesis of high-grade serous ovarian cancer by regulating the TGF-β/Smad pathway. 50 The clinical data suggested that TOP2A status might predict activity of pegylated liposomal doxorubicin in patients with epithelial ovarian cancers. 25 A study by Gulec et al showed that TOP2A expression was found to be related to poor OS of ovarian cancer patients, and was associated with platinum resistance.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Zhang et al showed that overexpressed SALT4 promotes the metastasis of gastric cancer by activating the TGF-β/Smad signaling pathway. 32 Also, Gao et al claimed that Topoisomerase II (TOP2A) aggravates the progression of advanced ovarian cancer by activating TGF-β/Smad, 33 suggesting that inhibiting the TGF-β/Smad signaling pathway may be a novel method for cancer treatment. Some scholars have found that the activation of down-regulated miR-542-3p on the TGF-β/Smad signaling pathway mediates hepatocellular carcinoma progression.…”
Section: Discussionmentioning
confidence: 99%